2019
DOI: 10.1002/da.22888
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state amplitude of low‐frequency fluctuation is associated with suicidal ideation

Abstract: Background: Identifying brain activity patterns that are associated with suicidal ideation (SI) may help to elucidate its pathogenesis and etiology. Suicide poses a significant public health problem, and SI is a risk factor for suicidal behavior.Methods: Forty-one unmedicated adult participants in a major depressive episode (MDE), 26 with SI on the Beck Scale for Suicidal Ideation and 15 without SI, underwent resting-state functional magnetic resonance imaging scanning. Twentyone healthy volunteers (HVs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Several previous studies used resting-state functional connectivity and other rs-fMRI measures to map dysfunctional network architectures in suicide attempters 11 , 12 , suicide ideators 13 , 14 , and healthy relatives of suicide victims 12 . These studies suggest that functional connectivity is promising in the identification of brain dysfunctions associated with suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies used resting-state functional connectivity and other rs-fMRI measures to map dysfunctional network architectures in suicide attempters 11 , 12 , suicide ideators 13 , 14 , and healthy relatives of suicide victims 12 . These studies suggest that functional connectivity is promising in the identification of brain dysfunctions associated with suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Although neuroimaging studies on suicide behavior have seen significant advances, most studies have reported the results at the group level, making it challenging to apply the results in actual clinical settings (18,20,24,56). Machine learning technologies can play a vital role in this aspect, as they can assess patterns in large data volumes and make individualized predictions (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Recent fMRI studies have shown that psychiatric disorders with suicide attempts are linked to structural and functional abnormalities in distinct brain networks, especially the frontolimbic system (14). It has been suggested that the frontolimbic system is heavily involved in mood regulation, including anxiety, reactive aggression, impulsivity, and decision-making, and may constitute a major component of the diathesis of suicidality (15)(16)(17)(18)(19)(20). In particular, the amygdala plays critical roles in emotional reactions, decision-making, and memory processing, all of which may be related to suicide (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent resting-state studies assessing changes in large-scale functional brain networks associated with suicide risk in adults have reported similar networks of brain regions. For example, resting-state studies of SI in adults diagnosed with MDD have found network changes in the hippocampus, thalamus, caudate ( 66 ), and anterior insula ( 72 ) associated with SI scores. In addition, altered seed-based connectivity has been found in the hippocampus, thalamus, and temporal lobe ( 69 ) as well as the inferior frontal, orbital, and parietal lobes ( 75 ).…”
Section: Neurobiological Markers Of Suicidal Thoughts and Suicide Rismentioning
confidence: 99%